Development new radiopharmaceutical based on 5-thio-d- glucose labeled technetium-99m; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Skuridin V. S. Viktor Sergeyevich; Ilina E. S. Elena Sergeevna; Rogov A. S. Alexander Sergeyevich; Nesterov E. A. Evgeny Alexandrovich; Sadkin V. L. Vladimir Leonidovich; Larionova L. A. Lyudmila Aleksandrovna; Varlamova N. V. Natalya Valeryevna; Zelchan (Zeltchan) R. V. Roman Vladimirovich (2016, 2016)
Title screen